2012
DOI: 10.1103/physrevlett.108.248001
|View full text |Cite|
|
Sign up to set email alerts
|

Flow Rate of Particles through Apertures Obtained from Self-Similar Density and Velocity Profiles

Abstract: ''Beverloo's law'' is considered as the standard expression to estimate the flow rate of particles through apertures. This relation was obtained by simple dimensional analysis and includes empirical parameters whose physical meaning is poorly justified. In this Letter, we study the density and velocity profiles in the flow of particles through an aperture. We find that, for the whole range of apertures studied, both profiles are self-similar. Hence, by means of the functionality obtained for them the mass flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

35
160
3
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 179 publications
(245 citation statements)
references
References 23 publications
35
160
3
2
Order By: Relevance
“…The method is similar to that found in Ref. [24]. The vertical component of the speed v y is found by projection of the displacement vectors on the y-axis.…”
Section: High Gravity: 3d and 2d Set-upmentioning
confidence: 72%
See 3 more Smart Citations
“…The method is similar to that found in Ref. [24]. The vertical component of the speed v y is found by projection of the displacement vectors on the y-axis.…”
Section: High Gravity: 3d and 2d Set-upmentioning
confidence: 72%
“…A fine analysis can be found in the Ref. [24] and is also supported by the arch formation analysis [25,26].…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Shortly after, Janda et al [17] reported an experimental study of a discharge of monodisperse 1-mm diameter stainless steel beads in a twodimensional silo. By means of an image processing technique, they measured vertical velocity v z and solid fraction φ profiles at the outlet for a wide range of apertures.…”
Section: Introductionmentioning
confidence: 99%